Analysis of body composition and autonomic function of the heart of schools from northern Mexico by gender - Hernández-Pérez, Héctor Alan; Hernández-Cruz, Germán; Rangel-Colmenero, Blanca Rocío; Quezada-Chacón, José Trinidad; Cruz-Castruita, Rosa María (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
Normative values of body composition (CC) and autonomic profile of Mexican schoolchildren are presented. The design corresponds to a study with a quantitative, descriptive approach. The CC was determined using the Poortmans and Slaughter equation, the HRV was in records of short duration. Significant differences were found in muscle mass when comparing: 13.13 ± 3.57kg for women vs 15.79 ± 3.50kg for men with a significance of p = .01. The autonomic profile did not show significant differences, the mean of the mean R-R intervals (MRR) was 616.16 ± 81.52 ms in girls and 611 ± 72.27 ms in boys.